Coalitions: A practice framework for sustainable development - Lombard, A; Janse van Rensburg, A (Social Work/Maatskaplike Werk, 2001)
1. INTRODUCTION Without partnerships it would be impossible for social service organisations to take up the challenge of making a policy shift from fragmented, specialist services to developmental, integrated services . In the opening address at the International Council for Social Welfare Conference, the Minister of Social Development, Dr Skweyiya, emphasised that governments and organisations of civil society need to respond in a more co-ordinated and strategic manner to the, widespread human poverty and decline of financial resources in many developing countries (Skweyiya, 2000 :2). At the foundation of partnership lies the reality of scarce and diminishing resources . Matube (2000b: 1) supports the opinion that sustainable development can take place and be facilitated only in the context of resource mobilisation. According to the Business in Community Report, sustainable development means adopting an integrated approach and striking a balance between environmental, social and economic considerations (Matube, 2000b:8) . According to this author there are various principles applicable to effective resource mobilisation for sustainable development of which partnerships are one example.